HPV vaccination to prevent oropharyngeal carcinoma: What can be learned from anogenital vaccination programs?. Issue 12 (December 2015) - Takes, Robert P.; Wierzbicka, Małgorzata; D'Souza, Gypsyamber; Jackowska, Joanna; Silver, Carl E.; Rodrigo, Juan P.; Dikkers, Frederik G.; Olsen, Kerry D.; Rinaldo, Alessandra; Brakenhoff, Ruud H.; Ferlito, Alfio
Highlights: We review the role of HPV vaccination in the prevention of head and neck squamous cell carcinoma (HNSCC) with special emphasis on OPC. The value of vaccination for prevention of OPC and possibly as an adjuvant treatment is still an open question. Evidence to date supports the possibility that HPV vaccination may prove to be effective in reducing the incidence of OPC. Summary: Human papillomavirus (HPV) infections are well known causes of anogenital cancers. Recent studies show that HPV also plays a role in oropharyngeal cancer (OPC). A review on the role of HPV vaccination in the prevention of head and neck squamous cell carcinoma (HNSCC) with special emphasis on OPC was conducted and available vaccines and vaccination strategies in HNSCC and OPC are discussed. Prophylactic vaccination is known to be effective for prevention of anogenital HPV infection and precursor lesions in the cervix and anus. While the value of vaccination for prevention of OPC and possibly as an adjuvant treatment is still an open question, evidence to date supports the possibility that HPV vaccination may prove to be effective in reducing the incidence of this malignancy.